Associations between genetic polymorphisms in interleukin-10 and hematological oncology: evidence from a meta-analysis. Issue 4 (2nd April 2020) - Hong, Pan; Feng, Wei-Ying; Fu, Lei-Hua; Jin, Jing; Fu, Jia-Ping
ABSTRACT: Background: Associations between polymorphisms in interleukin-10 ( IL-10 ) and hematological oncology were already explored by many genetic association studies, with controversial findings. The aim of this meta-analysis was to more comprehensively analyze associations between polymorphisms in IL-10 and hematological oncology by combing the results of all relevant studies. Methods: Eligible articles were searched from Pubmed, Embase, WOS and CNKI. The latest literature searching update was performed on 8 October 2019. We used Review Manager to combine the results of eligible studies. Results: Forty-one articles were included in this meta-analysis. IL-10 rs1800890 polymorphism was found to be significantly associated with hematological oncology under AA vs. TT+TA (recessive comparison, OR = 1.12, 95% CI 1.02–1.24), and rs1800896 polymorphism was also found to be significantly associated with hematological oncology under AA vs. AG+GG (dominant comparison, OR = 0.89, 95% CI 0.83–0.95) in overall combined analyses. In subgroup analyses, we observed positive results for rs1800871 (recessive comparison), rs1800872 (dominant, recessive and allele comparisons), and rs1800896 (dominant and allele comparisons) polymorphisms in the non-Hodgkin's lymphoma (NHL) subgroup. Besides, we also detected positive associations between rs1800872 polymorphism and acute leukemia (AL) (dominant and recessive comparisons) and found significant associations between rs1800896 polymorphism and chronic leukemia (CL) (recessive comparison). Conclusion: In summary, this meta-analysis demonstrated that IL-10 rs1800890, rs1800896, rs1800871 and rs1800872 polymorphisms may confer susceptibility to hematology oncology, especially for NHL.